Penerapan Hukum Pidana Militer Terhadap Anggota TNI Yang Melakukan Tindak Pidana Desersi - Musthang Wijaya Kusuma; Ali Masyhar (Legalita, 2026)
This study examines the application of military criminal law to the crime of desertion within the Indonesian National Armed Forces (TNI), emphasizing normative, sociological, and operational dimensions and their implications for discipline, organizational effectiveness, and civil-military relations. Desertion is understood not merely as an administrative violation, but as a betrayal of the soldier's oath that can undermine the command structure, lower unit morale, and threaten the success of defense missions. Analysis was conducted through a normative-juridical approach using library research on Law Number 34 of 2004 on the TNI, Law Number 31 of 1997 on Military Courts, and the Military Criminal Code (KUHPM). The findings confirm the importance of balancing strict law enforcement with a humanist approach in handling desertion cases. Additionally, preventive strategies based on ideological guidance, psychological counseling, improvement of soldier welfare, and the strengthening of unit solidarity need to be prioritized to minimize desertion. Effective prevention of desertion must be understood as an integral part of building TNI professionalism, ensuring not only military readiness but also social legitimacy and public trust.